Rekonstruksi Konsep Uang Dalam Ekonomi Islam: Kritik Terhadap Sistem Moneter Modern Berbasis Maqāṣid Al-Sharī‘ah - Romli, Mohammad (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to reconstruct the concept of money in Islamic economics through the Maqāṣid al-Sharī‘ah approach as a critical response to the modern fiat-based monetary system. The contemporary monetary system is widely perceived to exhibit fundamental structural weaknesses, including persistent inflationary pressures, the proliferation of speculative financial activities, and widening inequality in wealth distribution. These conditions indicate a deviation in the function of money from its essential role as a medium of exchange toward becoming a tradable commodity subject to speculation. This research adopts a qualitative method using a library research approach. Data were collected through an extensive review of classical Islamic economic texts, peer-reviewed academic journals, and official reports from national and international financial institutions. The data were analyzed using a descriptive-analytical method integrated with a normative Maqāṣid al-Sharī‘ah framework, which encompasses the preservation of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl). The findings reveal that, within Islamic economics, money should be restored to its fundamental roles as a medium of exchange and a unit of account, than as a commodity and a speculative instrument. The reconstruction of the concept of money based on Maqāṣid al-Sharī‘ah emphasizes value stability, equitable distribution, and the prohibition of riba and gharar practices. Therefore, this study highlights the urgency of reforming the global monetary system toward a more just, stable, and sustainable framework in line with Islamic principles.